Evaluación inicial al sg-sst en el instituto pedagógico - Suarez Gil, Hernando (Universidad Antonio Nariño, 2023)
The Colombian state, being a member of the ILO, has ratified several treaties related to occupational health and safety (OSH), which today are part of the block of constitutionality and with which the regulations that must be meet companies in different economic sectors. Consequently, the Decree 1072 of 2015, contemplates the obligations of the employer or contractor regarding the implementation of the occupational health and safety management system (SG-SST) and in accordance with the decree in question, resolution 0312 of 2019, in which the minimum OSH requirements that are a duty were established comply with the companies, being in accordance with the economic classification and the amount of workers.